ANALISIS KOMUNIKASI PERSUASIF DALAM MENCEGAH BULLYING PADA REMAJA : KAJIAN LITERATUR - Azzah Kamila; Najwa Zahratunnisa; Keiza Madinatuz A (CV. Denasya Smart Publisher, 2025)
Bullying among adolescents is a serious issue that significantly affects victims’ mental health, social development, and academic performance. This study aims to examine the role of persuasive communication in preventing bullying through a literature review approach. The findings indicate that persuasive communication strategies implemented by teachers, parents, and caregivers are effective in shaping adolescents’ attitudes and behaviors. Empathetic, educational, and consistent communication techniques increase awareness of the harmful effects of bullying and foster a safe and supportive social environment. Persuasive communication also strengthens interpersonal relationships and promotes moral values, which are essential for shaping positive adolescent character. Therefore, this approach is recommended as a key strategy in sustainable bullying prevention.